A Descriptive Analysis of Tactical Casualty Care Interventions Performed by Law Enforcement Personnel in the State of Wisconsin, 2010-2015. Issue 3 (21st February 2017) - Stiles, Chad M.; Cook, Christopher; Sztajnkrycer, Matthew D.
Abstract: Introduction: Based upon military experience, law enforcement has developed guidelines for medical care during high-threat conditions. The purpose of the current study was to provide a descriptive analysis of reported outcomes of law enforcement medical interventions. Methods: This was a descriptive analysis of a convenience sample of cases submitted to the Wisconsin Tactical Medicine Initiative (Wisconsin USA), after the provision of successful patient care, between January 2010 and December 2015. The study was reviewed by the Mayo Foundation Institutional Review Board (Rochester, Minnesota USA) and deemed exempt. Results: Nineteen agencies submitted information during the study period. Of the 56 episodes of care reported, four (7.1%) cases involved care provided to injured officers while 52 (92.9%) involved care to injured civilians, including suspects. In at least two cases, on-going threats existed during the provision of medical care to an injured civilian. Law enforcement rendered care prior to Emergency Medical Services (EMS) arrival in all but two cases. Conclusions: The current case series demonstrates the life-saving potential for law enforcement personnel trained and equipped under current Tactical Combat Casualty Care (TCCC)/ Committee on Tactical Emergency Casualty Care (C-TECC) tactical casualty care guidelines. Although originally developed to save the lives of wounded combat personnel, in the civilian sector, the training appears more likely to save victims rather than law enforcement personnel. CM Stiles, C Cook, MD Sztajnkrycer .A descriptive analysis of tactical casualty care interventions performed by law enforcement personnel in the State of Wisconsin, 2010-2015 .Prehosp Disaster Med .2017 ;32 (3 ):284 –288 .